Tycon: Pani-Tyre Dust as a Conductive Polymer for Bomb Sensor - Phua, Jin Luen; Chong, Yee Ling; Saw, Lip Teng; Teo, Siew Cheng (Universiti Malaysia Perlis (UniMAP), 2010)
Student Affairs & Alumni Department, Universiti Malaysia Perlis had successfully organized ENVEX 2010 (Engineering Invention and Innovation Exhibition 2010) with collaboration of Ministry of Higher Education (MOHE) and Ministry of Science, Technology and Innovation (MOSTI). ENVEX 2010 was held from 2nd to 4th April at SRJK(C) Khoon Aik Hall, Kangar, Perlis.